Sense of Humor in Harper Lee's To Kill a Mockingbird - Ali, Dlnya Abdalla Mohammed (Sulaimani Journal for Humanities, 2021)
Harper Lee in To Kill a Mockingbird (1960) explains how serious events can be underlined enough for attracting the attention of the readers. This motive had been fulfilled by the novelist with the help of adding a "sense of humor" in it along with the illustration of pathos. The book largely focuses on the social and racial injustices perpetrated against the blacks in the early 1900s American southern community of Alabama. While the story covers serious issues of the American dark past during the Great Depression era, humor is a major part of the novel. Thus, the novelist aims to ensure that all the information she tried to suggest is precisely understood by the readers, wherein, they feel glad enough to go through it. This is the only way through which, the book, presently, attains an important role in the American culture and people from varied parts of the world can enjoy the details involved in the novel. This textual analysis is a threadbare study of some different parts of the book and interpreting the meaning and the intent behind them to depict how Lee's novel has applied humor successfully to make light of serious subject matters such as corrupt accumulation of wealth, social injustices, and personal immoralities during the early twentieth-century American south.
Keywords: Sense of Humor; American Culture; Harper Lee; To Kill a Mockingbird